Challenges and Technologies in Reservoir Modeling (Communications in Computational Physics, 2009)
Reservoir modeling is playing an increasingly important role in developingand producing hydrocarbon reserves. In this paper, we provide a brief overview ofsome main challenges in reservoir modeling, i.e., accurate and efficient modeling ofcomplex reservoir geometry and heterogeneous reservoir properties. We then presentmodeling techniques we recently developed in addressing these challenges, includinga method for generating constrained Voronoi grids and a generic global scale-upmethod. We focus on the Voronoi gridding method, which is based on a new constrainedDelaunay triangulation algorithm and a rigorous method of adapting Voronoigrids to piecewise linear constraints. The global scale-up method based on genericflows is briefly described. Numerical examples are provided to demonstrate the techniquesand the advantage of combining them in constructing accurate and efficientreservoir models.
Keywords: Reservoir modeling; grid generation; grid adaptation; global scale-up.